The statistical analysis of the dynamic performance of a gear system considering random manufacturing errors under different levels of machining precision. (March 2020) - Guo, Fang; Fang, Zongde
Gear manufacturing error is one of the main sources of vibration and noise in gears; its influence on the dynamic transmission behaviour of gear systems is a research hotspot. In the current study on the effect of the manufacturing errors, the processing methods of the errors are mostly rough or hypothetical, so the analysis results cannot provide high reference value. This paper proposes a distinctive method to analyse the vibration response of helical gears in the presence of random manufacturing errors and modifications. The presented study performs tooth contact analysis (TCA) with the real tooth surface containing the random tooth profile error and the modification and performs loaded tooth contact analysis (LTCA) based on the superposition of the random pitch error and the initial gap between mating teeth obtained by TCA. Furthermore, the dynamic excitations, including time-varying mesh stiffness and meshing impact, are computed using the above-mentioned TCA and LTCA. The processing method for the manufacturing errors in this paper is reasonable and close to the actual situation of gear engagement. Using this proposed method, statistical analysis was carried out under machining accuracy grades 5, 6 and 7 to show the effect of the different distributions of random manufacturing errors on the gear vibration. The analysis results are of practical significance and provide references for the design and vibration control of gear drive systems.